The Sensation of Security : Private Guards and Social Order in Brazil - Robb Larkins, Erika, 1977- (Book collections on Project MUSE., 2023)
"Drawing on long term ethnographic research with security laborers, managers, company owners, and elite global consultants, The Sensation of Security examines the provision of security in Rio from the perspective of security personnel, providing an analysis of the racialized logics that underpin the ongoing work of securing the city"--